CFD modeling of a mini-pilot scale CO2 hydrogenation to hydrocarbons reactor using both direct and indirect pathway-based kinetic model - Jung, Yubeen; Min, Ji Eun; Park, Hae Gu; Jun, Ki Won; Kim, Jeong Rang; Jeon, Mingyo; Park, Myung June (Journal of CO2 Utilization, 2024)
Both indirect CO2 hydrogenation (reverse water gas shift (RWGS) followed by CO-based Fischer-Tropsch synthesis (FTS)) and direct CO2-based FTS were considered for CO2 hydrogenation, and a kinetic model for the chain-length distribution of hydrocarbon products was developed. For independent estimation, the kinetic parameters were estimated by fitting the experimental data using powder catalysts under various conditions, mainly including CO/CO2 ratios. The contribution of indirect CO2 hydrogenation (RWGS followed by CO-FTS) was more favorable than that of direct CO2-FTS, and CO2 conversion and product selectivity were significantly dependent on the temperature and hydrogen fraction. The effectiveness factor was estimated for the pellet-type catalysts, and values less than one validated the existence of mass-transfer resistance. Computational fluid dynamics (CFD) modeling was used to simulate the three-dimensional thermal behaviors of a mini-pilot-scale reactor with a substantially large diameter loaded with a pellet-type catalyst and inert materials. Both a low catalyst loading in the early stage of the reactor and the use of an additional inner cooling tube showed a stable temperature profile, with the peak temperature maintained below 350 °C (the critical temperature to prevent the thermal decomposition of chemicals) and fast heating of cold feed in the early stage. The CFD results with no inner tube showed thermal runaway in the second reactor, and the simulation with arbitrarily reduced heat of the reaction (70 % of the actual value) resulted in a peak temperature higher than 410 °C. Further quantitative analysis indicated that the no-inner-tube case's reduced heat transfer area per unit volume was responsible for its thermally unstable behavior.
Keywords: CO2 hydrogenation; Computational fluid dynamics modeling; Fischer Tropsch; Inner tubes; Kinetic models; Parameters estimation; Peak temperatures; Pellet type catalysts; Tropsch synthesis; Water-gas shifts; CFD modeling; CO2 hydrogenation; Fischer-Tropsch; Kinetic model; Parameter Estimation